The Effects of Colonialism toward the Timorese as depicted in Nesi’s Orang-Orang Oetimu - Catharina Brameswari; Tatang Iskarna; Monica Angela Nadine Titaley (Universitas Sanata Dharma, 2022)
This research scrutinizes the effects of colonialism toward the Timorese in Oetimu as depicted in the novel of Orang-Orang Oetimu by Felix K. Nesi. From the perspective of postcolonial criticism, the combination of the invasion of the Portuguese, Japanese, and Indonesian in East Timor leaves changes in social structure and relations among the Timorese. This study aims to unveil from postcolonial view, especially Said, Gandhi, Foulcer and Day, the destructive cultural and social effect, clash of local parties, and hidden colonial power which still exists in the Timorese society. Colonialism in East Timor operated by Portuguese, Japan, and Indonesia brought about physical, social, and cultural conflicts. Portuguese colonialism impacted on the socio-political friction among Timorese and destructive vanishing of their culture. Japanese colonialism left trauma amongst them as physical oppression was often used to have domination over the people. Indonesian invasion also resulted in horizontal conflicts amongst the Timorese. Violence and corrupt culture became new perspective in solving the problems. Presenting the colonial conflicts and destructive cultural effects, the novel voices postcolonial discourse that the effect of colonialism can last long and its ideology of binary opposition and cultural justification of domination in the name of civilization can be reproduced.